2015
DOI: 10.1158/0008-5472.can-14-2637
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between p53 Mutation and a Somatic HDMX Biomarker Better Defines Metastatic Potential in Breast Cancer

Abstract: TP53 gene mutation is associated with poor prognosis in breast cancer, but additional biomarkers that can further refine the impact of the p53 pathway are needed to achieve clinical utility. In this study, we evaluated a role for the HDMX-S/FL ratio as one such biomarker, based on its association with other suppressor mutations that confer worse prognosis in sarcomas, another type of cancer that is surveilled by p53. We found that HDMX-S/FL ratio interacted with p53 mutational status to significantly improve p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…RASSF1A is one of the most commonly epigenetically inactivated genes in human malignancies. RASSF1A CpG island methylation has been shown to correlate with early cancer onset in several tumour types including lung cancer (Grawenda et al , ; Pefani et al , ). We and others have shown that RASSF1A inactivation results in genomic instability and increased radio‐sensitivity (Dote et al , ; Yee et al , ; Pefani et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…RASSF1A is one of the most commonly epigenetically inactivated genes in human malignancies. RASSF1A CpG island methylation has been shown to correlate with early cancer onset in several tumour types including lung cancer (Grawenda et al , ; Pefani et al , ). We and others have shown that RASSF1A inactivation results in genomic instability and increased radio‐sensitivity (Dote et al , ; Yee et al , ; Pefani et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…While the oncogene Ki67 was significantly decreased, the oncogenes p53 and ELF5 were significantly increased. Grawenda et al 25 reported that p53 mutation could represent the prognosis and harbor potential utility as a clinical tool. Si et al 26 found that the expression of GATA3 is concurrently downregulated during breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Fernandes et al 28 also reported that PGR, ESR1, human epidermal growth factor-2, and Ki67 could act as the prognostic biomarker in different molecular subtypes of breast cancer. Comparing the above studies, 25 28 we systematically analyzed the key molecules or biomarker, which could provide the targeting pathway for the therapy in clinical.…”
Section: Discussionmentioning
confidence: 99%
“…This was clearly correlative in osteosarcoma and breast cancers [17, 21]. However, we did not observe any correlation between MDM4-S expression and p53 mutation status in the human B-CLL samples (Figure 1).…”
Section: Discussionmentioning
confidence: 70%
“…The MDM4-S transcript potentially encodes a truncated Mdm4 protein carrying only the N-terminal p53-binding domain along with 13 novel amino acids [16]. Overexpression of MDM4-S has been linked to poor prognosis in osteosarcoma, soft tissue sarcoma, breast cancer, glioblastoma, melanoma, and chronic lymphocytic leukemia [17-21]. MDM4-S lacks an internal autoinhibitory sequence [22] and previous overexpression studies indicated that nuclear localized MDM4-S acts as a potent inhibitor of p53 activity and thus likely functions as an oncogene [15, 16].…”
Section: Introductionmentioning
confidence: 99%